Compression Strength Concrete with Pond Ash Lati Berau - Tumingan Tumingan; Muhammad Wihardi Tjaronge; Victor Sampebulu; Rudy Djamaluddin (IPTEK Journal of Proceedings Series, 2017)
Handling of coal burning waste of thermal power plant in Lati, Berau district, East Kalimantan province, which is recommended by the department of environmental impact management is to dispose the coal ash into pools flowed water so that coal ash did not fly and cause air pollution. As known that coal ash waste is included hazardous and toxic waste, therefore managing it carefully is a necessity. Sediment or heap of coal ash in the sedimentation pond that is flowing with water is called Pond Ash. This study is conducted by utilizing the pond ash as a replacement material in the concrete mix. The effect of the use of pond ash as partial replacement of sand, fine aggregate in the concrete mix, is studied using cylindrical specimen with a diameter of 100 mm and a height of 200 mm. Specimens were made by taking the ratio of the percentage of pond ash of 0%, 5%, 10%, 15% and 20% of the mixture of concrete with the constant water cement ratio 0.49 which is based on the results of normal concrete mix design. The compressive strength test of concrete was conducted at ages 1, 3, 7, 14, 28 and 90 days. The test results of compressive strength of concrete obtained showed an increase in compressive strength in accordance with the addition of pond ash in the mix. The adding of pond ash in the mix affected the increasing in the compressive strength of concrete, and the optimum strength is obtained in the ratio of 17% pond ash, which increased to 26.08 MPa from 25.05 MPa for concrete with and without pond ash mixes respectively, or increased by 4.12%. This increase is not significant and cannot be used as a reference, however, by the results of this study it can be concluded that the pond ash waste can be utilized for the manufacture of concrete as a partial replacement of sand.